History of the Kyiv Philosophical School in the oral recollections of its creators (the era of The Executed Renaissance) - H. V. Vdovychenko (Ukrainian Cultural Studies, 2021)
The article deals with the revival by the Kyiv philosophical school of the second half of the 20th century of the first academic research on the history of Ukrainian philosophy, interrupted in the 1930s. These studies were a component of the innovative project of P. Kopnin and V. Shynkaruk as the directors of the H. Skovoroda Institute of Philosophy and were carried out in the contradictory conditions of the Khrushchev "thaw" and stagnation by the illustrious generation of the philosophers-Sixtiers of the Ukrainian SSR. Their memories were mainly realized in T. Chaika’s project "The Philosophers’ Oral Histories" in the form of autobiographical reconstructions of S. Krymskyi, P. Yolon, V. Horskyi and M. Popovych and also in the corresponding reconstructions of their colleagues Y. Golovakha, M. Kashuba and Y. Stratii, carried out by the Student Society of Oral History of Philosophy of Taras Shevchenko National University of Kyiv. The study, mainly, of these memories testifies to the general attention of these scholars to Ukrainian studies as one of the main vectors of the research work of the mentioned institute in the second half of the 20th century. Analysis of their contribution to the study of the history of Ukrainian philosophy on the basis of the alternative data received from them in this projects already in independent Ukraine significantly changes the traditional vision of started by the Kyiv philosophical school in the 1950s censored study of the "philosophical front" of the Ukrainian SSR during the Executed Renaissance. These interviews with S. Krymskyi, E. Golovakha, V. Horskyi, as well as the interviews and memoirs of their colleagues, revealed a little-known problematic interpretation by the creators of the Kyiv philosophical school of their place and role in the history of Ukrainian philosophy as the leading heirs of started in the 1920s institutionalization of the domestic national philosophical tradition.